PENGARUH INOVASI, KEPEMIMPINAN VISIONER, DAN NETWORKING PADA ORGANIZATIONAL CITIZENSHIP BEHAVIOR PEGAWAI NEGERI - Enggal Sriwardiningsih; Ghina Chantika Chaerunissa (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2019)
The purpose of this study was to analyze the influence of employee competence, innovation, visionary leadership and networking on OCB in Sekretariat Kabinet. The method that used for this research is survey method with quantitative data as a primary data. This type of research is associative research. The data is analyzed with Partial Least Square using SmartPLS 3.0. Unit analysis target is individual from the employees of Deputi Dukungan Kerja Kabinet. Based on the research result shows that: 1) employee competence has significant and negative influence on organizational citizenship behavior, 2) The innovation has significant and positive influence on organizational citizenship behavior, 3) The visionary leadership has significant and positive influence on organizational citizenship behavior, 4) The networking has significant positive influence on organizational citizenship behavior.